The power of fiction and its controversies in Azar Nafisi’s portrayals of a new compliant nationality (ENTHYMEMA, 2020)
According to Anderson’s positions on nation and nationalism as cultural artifacts, Azar Nafisi’s literary memoirs show a controversial case study, focused on the ambiguities of the exile discourse and of the so-called «imaginative knowledge». Through the lens of a recurring celebration of Western myths of freedom, a series of stereotypes and paradoxes will be examined, in relation to the censorship experienced by the author under the Islamic Republic of Iran. Moreover, Nafisi’s juxtaposition of political and literary perspectives will be shown as an ambivalent narrative strategy, despite her search for a true self without any ideological engagement. In the end, the explored duality between oriented dissertations and pure imaginative recreations will enable to reconsider Nafisi’s memoirs as committed depictions of a Westernized national legacy.
Keywords: Diaspora; Identity; Nation; Migration